Impact of the Adopted Financial Processes for Carrying Out Green Energy Projects in Georgia - Zhakupova, Aizada; Aigerim, Lambekova; Elmira, Syzdykova; Dinara, Syzdykova; Azamat, Zhanseitov (International Journal of Energy Economics and Policy, 2021)
Green energy is considered the backbone for all the environmental strategies as it impacts the organizations in three key areas, such as the economy, society, and environment. Green energy projects have emerged as the sustainable drivers of economic elevation for a country, replacing the conventional energy sources that damage the ecology to a great extent. In this paper, the primary purpose is to overview the financial processes to pursue green energy. Moreover, this paper has analyzed all the financial mechanisms required in Georgia to carry out green energy projects. This paper has also compared Georgia’s economic mechanisms with those of another developing country, Kazakhstan. For this purpose, this paper has gathered the secondary sources of data to identify the financial processes and the associated risks of Georgia’s financial operations for pursuing the green energy processes. For understanding Georgia’s financial mechanisms, this paper has incorporated descriptive analysis tools and regression analysis. Keywords: financial development, economic progress, energy consumption; financial strategy; financial stability budget; renewable energy. JEL Classifications: Q16, 016, 044 DOI: https://doi.org/10.32479/ijeep.10766